Factor the following expression 27y3 -343
1 answer:
27y^3 -343 starts out with 27y^3, and 343 is the cube of 7. Thus, we know immediately that 27y3 -343 is the diffeence of two squares.
The appropriate rule is a^3 - b^3 = (a - b)(a^2 + ab + b^2).
Here, we have 27y3 -343 = (3y - 7)(9y^2 + 12y + 49)
You might be interested in
Answer:
80/7 simplified its 11 3/7
Step-by-step explanation:
lmk if you need an explanation! :]
Answer:
55.04 m 2
Step-by-step explanation:
I am 100% sure this is right.
please mark me as brainlest
y=4x-3(4,1)x2 (2-0) perpedkdkke
Answer:
x + 3 + 45° = 180°. isosceles triangle
x = 180° - 45°-3°
x = 132°
90° + x = 180°
x =180° - 90°
x = 90°
When you multiply 35 x 40 = 1400
:)